Decolonising Blue Spaces in the Anthropocene Freshwater management in Aotearoa New Zealand - Parsons, Meg; Fisher, Karen; Crease, Roa Petra (Palgrave Studies in Natural Resource Management, 2021)
This open access book crosses disciplinary boundaries to connect theories of environmental justice with Indigenous people's experiences of freshwater management and governance. It traces the history of one freshwater crisis - the degradation of Aotearoa New Zealand's Waipā River- to the settler-colonial acts of ecological dispossession resulting in intergenerational injustices for Indigenous Māori iwi (tribes). The authors draw on a rich empirical base to document the negative consequences of imposing Western knowledge, worldviews, laws, governance and management approaches onto Māori and their ancestral landscapes and waterscapes. Importantly, this book demonstrates how degraded freshwater systems can and are being addressed by Māori seeking to reassert their knowledge, authority, and practices of kaitiakitanga (environmental guardianship). Co-governance and co-management agreements between iwi and the New Zealand Government, over the Waipā River, highlight how Māori are envisioning and enacting more sustainable freshwater management and governance, thus seeking to achieve Indigenous environmental justice (IEJ). The book provides an accessible way for readers coming from a diversity of different backgrounds, be they academics, students, practitioners or decision-makers, to develop an understanding of IEJ and its applicability to freshwater management and governance in the context of changing socio-economic, political, and environmental conditions that characterise the Anthropocene. Meg Parsons is senior lecturer at the University of Auckland, New Zealand who specialises in historical geography and Indigenous peoples' experiences of environmental changes. Of Indigenous and non-Indigenous heritage (Ngāpuhi, Pākehā, Lebanese), Parsons is a contributing author to IPCC's Sixth Assessment of Working Group II report and the author of 34 publications. Karen Fisher (Ngāti Maniapoto, Waikato-Tainui, Pākehā) is an associate professor in the School Environment, University of Auckland, New Zealand. Aotearoa New Zealand. She is a human geographer with research interests in environmental governance and the politics of resource use in freshwater and marine environments. Roa Petra Crease (Ngāti Maniapoto, Filipino, Pākehā) is an early career researcher who employs theorising from feminist political ecology to examine climate change adaptation for Indigenous and marginalised peoples. Recent publications explore the intersections of gender justice and climate justice in the Philippines, and mātuaranga Māori (knowledge) of flooding. .